Android Users Privacy Awareness Survey - Alani, Mohammed M. (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Having a share of over 80% of the smartphone market, Android has become an important mobile operating system that is used by billions of users on daily basis. With the widespread use of smartphones in general, and Android in specific, privacy concerns grow with that expansion in the user base. With the millions of applications being downloaded by users daily, it is becoming increasingly difficult to differentiate between the good and the bad in terms of security and privacy. In this paper, we present the results of a survey conducted among 4027 Android users worldwide. This survey was conducted to measure the awareness of Android users regarding their privacy. The study measures the users' interaction with the permissions required by different applications they install. The results of the survey show apparent weakness in the awareness of Android users regarding the privacy of their data.